Value of measuring suicidal intent in the assessment of people attending hospital following self-poisoning or self-injury. - Harriss, L; Hawton, K; Zahl, D (2005)
BACKGROUND: Self-harm is associated with a high risk of suicide. It is unclear whether suicidal intent at the time of self-harm is a risk factor for future suicidal behaviour. AIMS: To investigate the relationship between suicidal intent and patient characteristics, repetition of self-harm, and suicide. METHOD: Clinical and demographic data on 4415 patients presenting to hospital following self-harm between 1993 and 2000 were analysed. Suicidal intent was measured using the Beck Suicide Intent Scale (SIS). Follow-up information on repetition of self-harm and suicide was investigated for 2489 patients presenting between 1993 and 1997. RESULTS: Suicidal intent at the time of self-harm was associated with risk of subsequent suicide, especially within the first year and among female patients. Suicide was more strongly associated with scores on the circumstances section of the SIS than the self-report section. The association between repetition of self-harm and SIS scores was different for male and female patients. CONCLUSIONS: The measurement of suicidal intent in the assessment of self-harm patients is beneficial for the evaluation of future suicide risk. A shortened measuring scale might be useful in clinical practice.